The effect of TiO2 coating and coffee immersion on discoloration of thermoplastic nylon denture base - Rahmat Hidayat; Murti Indrastuti; Heriyanti Amalia Kusuma; Suparyono Saleh (Majalah Kedokteran Gigi Indonesia, 2018)
The thermoplastic nylon denture base material is prone to discoloration because its amide bonds absorb water easily. Titanium dioxide (TiO2) nanoparticle have long been used as a denture base coating. Meanwhile, coffee contains chlorogenic and tanic acid, which can change the color of denture bases. The purpose of this study was to examine the effect TiO2 coating and duration of coffee immersion on discoloration of thermoplastic nylon denture base. Samples consisted of 24 thermoplastic nylon in square-shaped (30 x 30 x 2 mm), divided into 4 groups (n = 6). They were control (without TiO2 coating) and treatment (with TiO2 coating) groups, which then were immersed in coffee solution for 15 and 30 days. Discoloration test was conducted using spectrophotometer by measuring the delta absorbance of light before and after coffee immersion. The result showed that the lowest delta absorbance was in the 15-day treatment group (0.011 ± 0.005) and the highest was in the 30-day control group (0.077 ± 0.027). Two-way ANOVA test showed that TiO2 coating and coffee immersion had an effect on discoloration of thermoplastic nylon (p <0.05). Post hoc LSD test showed that there were significant differences between the control and treatment group at 15 and 30 days of coffee immersion (p <0.05). In conclusion, TiO2 as a thermoplastic nylon denture base coating can reduce discoloration by coffee immersion for 15 and 30 days. There were no differences between 15 and 30 days of coffee immersion on thermoplastic nylon’s discoloration in the control and treatment groups.